A Safe Innovative Way to Increase the Resource Efficiency of the Meat Industry (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is known that the innovative development of any industry is directly related to the intensification of production, as a result of the use of improved, innovative techniques and technology, as well as new forms of production and labor organization, effective and full of available resources. provides an increase in utilization and labor productivity.the meat industry refers to activities aimed at the production of new or improved (in terms of quality, appearance and efficiency) products of the livestock industry. This activity arises as a result of scientific research and development or the use of best practices in order to modernize production and capture the market.In this article, hydroponics technology is analyzed as a safe innovative method of increasing the resource potential of the meat industry, and the possibilities of its application in Uzbekistan are analyzed.